Konservierungswissenschaft schreibt Geschichte Objektrestaurierung an der Angewandten - - Krack, Elisabeth (2012)
An overview of the academic courses of study and vocational trainings offered in the conservation and restoration of objects of decorative arts and metal in German-speaking countries points to a lack of continuity and identity. This is due to the fact that this field is a relatively young one and many universities have only offered degree courses since the 1990s. In Austria there are two Universities, the "Akademie der bildenden Künste" and the "Universität für angewandte Kunst". Both are located in Vienna and have a old-established academic experience. The long tradition particular to the field of restoration of objects of decorative arts at the University of Applied Arts Vienna is exceptionally. Early conservation and preservation research and restoration work started in the late 19th century. This is a distinctive feature, as other institutions with a similarly long history put their focus on the restoration of paintings and painting technique research instead. The "Kunstgewerbemuseum", todays Museum of Applied Arts Vienna, was founded 1863. In 1868 the school called "Kunstgewerbeschule" was attached. It is famous for its leading design-position during art nouveau an developed into todays University of Applied Arts Vienna. Both stood in close contact with the "K.K. Centralcommission". This historic preservation agency, established in 1850, concentrated in the preservation of monuments and historic buildings of the large Habsburg Empire. During the 19th century new emerging ideas of conservation where well known at "Kunstgewerbeschule" and "Kunstgewerbemuseum". Teaching staff at the school made in their annual reports notes of early restoration. But they did it as an additional business and therefore more detailed information is not given. Women in the studios for enamelwork (Adele von Stark) and the studio for textile work (Rosalia Rothansl) were about 1900 pioneers in field of object conservation. The first official class for conservation existed 1902 - 1910, named "Atelier für Kunstweberei und Restaurierung". A lot of information about the astonishing mordern ethics and methods in Conservation at that time can be extracted from two conferences that took place in Vienna: The First Arthistorical Congress in 1873 and the Enquete about Conservation of Art in 1904. Curators of the Museum of applied Arts and to a certain extent teaching staff of the "Kunstgewerbeschule" were involved with organisation and speeches. A new era for the conservation at University of Applied Arts Vienna started after World War Two. Otto Nedbal, a conservator experienced in metal crafts, was appointed at the university. He at first assumed the existing class for enamelwork. In 1964 he founded a new master class for restoration of metals and objects of enamel. But the content of teaching and the requirements for diploma thesis changed significant during the following forty years and this class evolved into today's Institute for Conservation and Restoration. The specialization of painting conservation was established by Nedbals successor Hubert Dietrich in 1980. In the course of a reorganization of the university in 2000 and the appointment of Gabriela Krist as head of the new conservation department, the new specializations of conservation of stone and textile were arranged.